CpG ODN‐induced matrix metalloproteinase‐13 expression is mediated via activation of the ERK and NF‐κB signalling pathways in odontoblast cells. (21st January 2013) - Zhang, J.; Zhu, Q. L.; Huang, P.; Yu, Q.; Wang, Z. H.; Cooper, P. R.; Smith, A. J.; He, W.
Abstract Aim To investigate the effects of CpG ODN (CpG oligodeoxynucleotides) to model the action of bacterial challenge on pulpal matrix metalloproteinase‐13 (MMP‐13) expression and elucidate the associated intracellular signalling pathways. Methodology Real‐time PCR was used to detect the effects of CpG ODN on MMP‐13 mRNA expression levels in a murine odontoblast‐lineage cell line (OLCs). The possible involvement of TLR9/MyD88, NF‐κB or MAPK pathways involved in the CpG ODN‐induced MMP‐13 expression was examined by real‐time PCR, transient transfection, luciferase activity assay and ELISA. Western blotting was performed to assay the phosphorylation of ERK at a range of time points. Results MMP‐13 was constitutively expressed in OLCs, and their exposure to CpG ODN significantly increased MMP‐13 expression. Pre‐treatment of OLCs with the inhibitory peptide MyD88, or chloroquine, attenuated the CpG ODN‐induced expression of MMP‐13. Treatment of the OLCs with CpG ODN increased NF‐κB‐luciferase activity. This activity was decreased by the over‐expression of a nondegrading mutant of IκBα (IκBαSR), although enhanced by the over‐expression of NF‐κB p65. MMP‐13 expression induced by CpG ODN was markedly suppressed by NF‐κB inhibitors (pyrrolidine dithiocarbamate, PDTC), IκBα phosphorylation inhibitors (Bay 117082) or IκB protease inhibitor (L‐1‐tosylamido‐2‐phenylethyl chloromethyl ketone, TPCK). The inhibitor of ERK1/2, U0126, but not inhibitors of p38 MAPK and JNK, SB203580 and SP600125, decreased CpG ODN‐mediated MMP‐13 expression. Conclusion The CpG ODN‐induced MMP‐13 expression in OLCs is mediated through TLR9, NF‐κB and the ERK pathway indicating that potentially the recognition of CpG ODN by TLR9 on odontoblasts may regulate the remodelling of injured dental pulp and hard tissues by inducing MMP‐13 expression.